Understanding Poverty Reduction Impacts with Innovative Monitoring and Evaluation - Garcia, Marito; Alderman, Harold; Rudqvist, Anders (World Bank, Washington, DC, 2012)
Monitoring and evaluation systems are often the least addressed component of project design, and implementation. Yet, such systems have considerable potential for enhancing the impact of projects, and the understanding of poverty reduction impacts. This note addresses what makes effective monitoring and evaluation, where both quantitative, and participatory methods are needed to assess a project's impact on poverty. It examines the case of the Uganda Nutrition and Early Childhood Development Project, a process-driven, locally prioritized program, being implemented by a network of nongovernmental organizations, that motivates communities, and provide information to project participants. The project relies on systematic monitoring of inputs and outputs, and, community participation in planning, and monitoring facilitates bottom-up feedback. The note further highlights a randomized experimental design, i.e., a baseline and follow-up surveys, that assess the impact of project activities, of communication and information, and of grassroots management training, and income generation activities for community welfare. The benefits of proactive monitoring and evaluation are that it enables timely inputs into management decision making, and that the quantitative methods used, are important determinants for assessing, and verifying a project's impact.